2021
DOI: 10.3892/ol.2021.12604
|View full text |Cite
|
Sign up to set email alerts
|

Pathways and role of MALAT1 in esophageal and gastric cancer (Review)

Abstract: Esophageal cancer (EC) and gastric cancer (GC) often have an unfavorable prognosis. Therefore, research is being conducted to identify the molecular mechanisms underlying the tumorigenesis and progression of GC and EC, and to indicate novel therapeutic targets and clinically applicable biomarkers. The dysregulations and roles of long non-coding RNAs (lncRNAs) have been widely reported, and current published literature has shown that lncRNAs play important regulatory roles in the carcinogenesis and progression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 39 publications
(71 reference statements)
2
16
0
Order By: Relevance
“…The disorder of MALAT1 expression has been identified to be of great significance for the prognosis and treatment of various cancers, such as lung cancer, hepatocellular cancer, nasopharyngeal cancer, colorectal cancer, and gastric cancer 25 . Notably, there was evidence showing that MALAT1 was up‐regulated in both tissues and cells of EC, suggesting the potential pathogenic role of MALAT1 in EC 18,26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The disorder of MALAT1 expression has been identified to be of great significance for the prognosis and treatment of various cancers, such as lung cancer, hepatocellular cancer, nasopharyngeal cancer, colorectal cancer, and gastric cancer 25 . Notably, there was evidence showing that MALAT1 was up‐regulated in both tissues and cells of EC, suggesting the potential pathogenic role of MALAT1 in EC 18,26 .…”
Section: Discussionmentioning
confidence: 99%
“…11 Besides, Hu et al 10 The disorder of MALAT1 expression has been identified to be of great significance for the prognosis and treatment of various cancers, such as lung cancer, hepatocellular cancer, nasopharyngeal cancer, colorectal cancer, and gastric cancer. 25 Notably, there was evidence showing that MALAT1 was up-regulated in both tissues and cells of EC, suggesting the potential pathogenic role of MALAT1 in EC. 18,26 In our work, inhibiting MALAT1 could reduce the viability of EC cells while advance the apoptosis, with the up-regulations of pro-apoptotic proteins (Bax and active caspase-3) and the down-regulation of anti-apoptotic protein (Bcl-2).…”
Section: Discussionmentioning
confidence: 99%
“…MALAT1 is an oncogene with high conservation degree, which promotes cancer development and regulates radio-sensitivity and chemo-sensitivity in cancer cells [ 9 , 31 ]. MALAT1 has been considered as the prognostic cytokine that initially marked to be the survival marker, due to that it is related to tumor migration, metastasis, and recurrence among NSCLC patients [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…In tumor cells, MALAT1 by targeting several transcription factors, growth factors, hormones, and epigenetic histone modifications can mediate cancer cell proliferation, tumorigenicity, autophagy, epithelial-mesenchymal transition (EMT), metastasis, and drug resistance phenotypes [ 28 31 ]. Recent studies elucidated the role of MALAT1 in CRC cell growth, migration, invasion, and metastasis [ 32 , 33 ]. MALAT1 was reported to target several CRC-related pathways such as Wnt/β-catenin, YAP, SOX9, RUNX2, Snail, EGF, PI3K/AKT/mTOR, P53, and VEGF [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%